Direct measurement of interface energies of magnesium aluminate spinel and a brief sintering analysis. Issue 13 (October 2017) - Pereira, Gilberto J.; Bolis, Karen; Muche, Dereck N.F.; Gouvêa, Douglas; Castro, Ricardo H.R.
Abstract: Surface and grain boundary energies are key parameters for understanding and controlling microstructural evolution. However, reliable thermodynamic data on interfaces of ceramics are relatively scarce, limiting the realization of their relevance in processes such as sintering and grain growth. In this work, the heat of sintering itself was used to quantify both surface and grain boundary energies in MgAl2 O4 spinel. Nanoparticles were compacted and heated inside a Differential Scanning Calorimeter (DSC) when densification and grain growth were observed. The evolved heat signal was quantitatively attributed to the respective microstructural evolution in terms of interfacial area change, allowing determination of average surface and grain boundary energies for MgAl2 O4 as 1.49 J m −2 and 0.57 J m −2, respectively. The data was then used to interpret the thermodynamics involved in density and grain growth during isothermal sintering of MgAl2 O4 .